Neutrophil‐to‐lymphocyte ratio as a prognostic indicator for overall and cancer‐specific survival in squamous cell carcinoma of the head and neck. Issue 10 (27th June 2020) - Ferrandino, Rocco M.; Roof, Scott; Garneau, Jonathan; Haidar, Yarah; Bates, Susan E.; Park, Yeun‐Hee A.; Bauml, Joshua M.; Genden, Eric M.; Miles, Brett; Sigel, Keith
Abstract: Background: Neutrophil‐to‐lymphocyte ratio (NLR) is a biomarker that is correlated with systemic inflammation and poor prognosis in solid tumors. We investigated the value of NLR in predicting survival in a large population of head and neck cancer patients in the United States. Methods: We performed a retrospective cohort study of Veterans Affairs patients with head and neck squamous cell carcinoma (HNSCC) diagnosed between January 2000 and December 2017. We compared 5‐year overall survival and cancer‐specific survival for different NLR tertiles using cox proportional hazards modeling with adjustment for covariates. Results: The primary cohort consisted of 14 644 subjects of which 99% were male. Relative to patients with NLRs in the lower tertile, patients with NLRs in the top tertile had an 71% increased hazard of all‐cause mortality ( P  < .001) and 44% increased hazard of cancer‐specific mortality ( P  < .001) at 5 years. Conclusions: Elevated NLR in HNSCC confers a poor prognosis.